EXPLORING 8TH GRADE STUDENTS’ EXPECTATIONS ON INTERCULTURAL-BASED SPEAKING MATERIALS TO PRACTICE LINGUISTIC FEATURES AND PEACE EDUCATION IN THE MERDEKA CURRICULUM - Deviani, Putu Maya Bertha (Lingua Scientia, 2024)
This study explored 8th-grade students' expectations regarding English speaking materials integrated with intercultural content and peace education within the Merdeka Curriculum. The research aimed to examine how these materials support both linguistic development and the promotion of tolerance, empathy, and cultural understanding. A mixed-methods approach was employed, involving 60 eighth-grade students from Jembrana, a culturally diverse area. Results indicated that students valued vocabulary, grammar, and pronunciation exercises but identified a significant gap in materials that address peace education, conflict resolution, and respect for differing perspectives. Additionally, students expressed a desire for innovative, engaging speaking activities and contextually relevant materials that reflect both local and global cultures. These findings suggest that current textbooks fall short of students’ expectations for building intercultural competence and peaceful communication skills. The study’s insights offer essential considerations for enhancing English speaking materials to better meet students’ linguistic and cultural needs, preparing them for meaningful intercultural interactions in diverse environments.